Oxidation of imidacloprid insecticide through PMS activation using CuFe2O4 nanoparticles: Role of process parameters and surface modifications - Núñez-de la Rosa, Yeison (2024)
The contamination of water bodies by synthetic organic compounds coupled with climate change and the growing demand for water supply calls for new approaches to water management and treatment. To tackle the decontamination issue, the activation of peroxymonosulfate (PMS) using copper magnetic ferrite (CuMF) nanoparticles prepared under distinct synthesis conditions was assessed to oxidize imidacloprid (IMD) insecticide. After optimization of some operational variables, such as CuMF load (62.5–250 mg L−1), PMS concentration (250–1000 μM), and solution pH (3-10), IMD was completely oxidized in 2 h without interferences from leached metal ions. Such performance was also achieved when using tap water but was inhibited by a simulated municipal wastewater due to scavenging effects promoted by inorganic and organic species. Although there was evidence of the presence of sulfate radicals and singlet oxygen oxidizing species, only four intermediate compounds were detected by liquid chromatography coupled to mass spectrometry analysis, mainly due to hydroxyl addition reactions. Concerning the changes in surface properties of CuMF after use, no morphological or structural changes were observed except a small increase in the charge transfer resistance. Based on the changes of terminal surface groups, PMS activation occurred on Fe sites.